Underpricing pada Saat IPO: Reputasi Underwriter, Profitabilitas, Solvabilitas, Umur Emiten, dan Earning per Share - Wening Isyfa Wafdani; Eny Kusumawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Underpricing is a situation where the share price in the primary market is lower than the share price in the secondary market. This study investigates the effect of underwriter reputation, profitability, solvency, company age and earnings per share on underpricing in non-financial companies listed on the Indonesia Stock Exchange during 2021-2023. The sampling technique used in this study was non-probability sampling and purposive sampling method. A total of 144 companies met the criteria as observation units. The analysis technique used is multiple regression analysis. The results of this study provide empirical evidence that the reputation of credit rating agencies, company age and earnings per share affect underpricing, while profitability and solvency have no effect on underpricing.